Pengaruh Kemauan Membayar, Kemampuan Membayar dan Kesadaran Membayar Masyarakat terhadap Pencapain Pendapatan BLUD Pengelolaan Air Bersih Kota Batam - Nurul Handayani; Sabri Sabri; Amirullah Amirullah (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the vital role of clean water services and the need to optimize operational revenue at BLUD UPT Water Supply Management in Batam City. The study aims to analyze the influence of willingness to pay, ability to pay, and payment awareness on BLUD revenue achievement. A quantitative associative approach was employed, involving a population of 29,047 customers. A sample of 100 respondents was determined using the Slovin formula, and data were analyzed via multiple linear regression using SPSS software. The results indicate that, simultaneously, all three independent variables significantly affect revenue achievement with an F-value of 56.825 and a significance of 0.000. Partially, willingness to pay (t=8.279), ability to pay (t=11.020), and payment awareness (t=10.435) also exert a significant influence. These findings imply that higher community payment behavior directly increases institutional revenue. It is recommended that BLUD improves service quality and payment socialization to ensure sustainable revenue achievement.